2022
DOI: 10.1186/s13063-022-06016-2
|View full text |Cite
|
Sign up to set email alerts
|

High-dose vitamin D substitution in patients with COVID-19: study protocol for a randomized, double-blind, placebo-controlled, multi-center study—VitCov Trial

Abstract: Background The coronavirus disease 19 (COVID-19) pandemic has caused millions of deaths, and new treatments are urgently needed. Factors associated with a worse COVID-19 prognosis include old age (> 65 years), ethnicity, male sex, obesity, and people with comorbidities. Furthermore, vitamin D deficiency was reported as a predictor of poor prognosis in patients with acute respiratory failure due to COVID-19. According to a recent clinical case series, vitamin D deficiency is a modifiable risk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Further, not taking any medicine, only vitamins and minerals taken as a supplement, was also effectively associated with the reduction in severity (OR: 0.8 (95% CI: 0.3–1.9) ( p = 0.005)) of COVID-19. Findings from this study are in good agreement with previous studies supporting that vitamins and minerals are associated with the improvement of health conditions of COVID-19-infected individuals [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 46 , 47 , 48 , 49 ]. Further, a study on the association of vitamin D with a reduced requirement of ICU, oxygen support and death number among hospitalized patients also supports our findings [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further, not taking any medicine, only vitamins and minerals taken as a supplement, was also effectively associated with the reduction in severity (OR: 0.8 (95% CI: 0.3–1.9) ( p = 0.005)) of COVID-19. Findings from this study are in good agreement with previous studies supporting that vitamins and minerals are associated with the improvement of health conditions of COVID-19-infected individuals [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 46 , 47 , 48 , 49 ]. Further, a study on the association of vitamin D with a reduced requirement of ICU, oxygen support and death number among hospitalized patients also supports our findings [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…Further, a study on the association of vitamin D with a reduced requirement of ICU, oxygen support and death number among hospitalized patients also supports our findings [ 49 ]. Recent studies on the role of vitamin D against COVID-19 have found various positive impacts [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] including a molecular mechanism of preventing COVID-19 [ 51 ], association with reduced risk of infection [ 45 ], prevention of infection and reduction in the severity of COVID-19 [ 45 , 48 ]. Other studies have found that both vitamin C and Zinc can also contribute to the prevention and treatment of COVID-19 [ 45 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further they pointed out that larger trials will be required. COVIT and VitCov are recent examples of multicentric controlled clinical trials in France and Switzerland respectively, probing the utility of vitamin D in COVID-19 management [ 170 , 171 ].…”
Section: Vit D Supplementation In Combination With Other Nutraceutica...mentioning
confidence: 99%
“…Serum vitamin D concentration is reported to serve as predictor of SARS-CoV-2 infection, which is independent of age, sex, race and attitude (Ilie et al 2020). In comparison to placebo, a single high dose of vitamin D is reported to have an immediate beneficial effect on hospitalized COVID-19 patients in terms of shortening the duration of hospitalization and reducing the need for mechanical ventilation (Jaun et al 2022) Although some progresses have been made in understanding the molecular basis of action of vitamin D, the total picture is not clear. However, enhanced expression of antimicrobial proteins, defensin and cathelicidin which are reported to play important role in the infection outcome process of various bacterial and viral agent (Kearns et al 2015;Fiske et al 2019;Tomaszewska et al 2022) is speculated to have an important role in vitamin D induced protective functions in SARS = CoV-2 infection.…”
Section: Sars-cov-2 Virus Infectionmentioning
confidence: 99%